Fetal Outcome Associated with COVID-19; Correlation between Ultrasound and Birth Measures in COVID-19 Pregnant Women - Osama Abel Azim Elgamal, Mai Ibrahim; Ragab, Mostafa Hassan; Makled, Ahmed Khairy (International Journal of Child Health and Nutrition, 2024)
Background: Coronavirus disease 2019 (COVID-19), caused by the virus SARS-CoV-2, was declared a global pandemic in March 2020. Pregnant women might be especially vulnerable to COVID-19 because the physiological changes in their cardiorespiratory and immune systems during pregnancy could alter their response to SARS-CoV-2 infection. Objective: to determine the association between SARS-CoV-2 infection and fetal outcomes, including SGA, FGR, preterm birth, and stillbirth. Methods: This prospective study was conducted at the Ultrasound and Fetal Medicine Unit of Ain Shams University Maternity Hospital, a tertiary care center, from October 2021 to January 2023. The study included 45 pregnant women diagnosed with COVID-19 during the first or second trimester of their current pregnancy. Additionally, a control group of 45 pregnant women who were not infected with COVID-19 was included. Both groups were selected based on predefined inclusion and exclusion criteria. Results: There were no statistically significant differences between the two groups regarding demographic characteristics, including age, body mass index, and parity. The timing of COVID-19 infection was nearly evenly distributed between the first and second trimesters. All cases in the infected group were non-hospitalized. No statistically significant differences were found between the groups regarding the need for induction or mode of delivery. Additionally, there were no significant differences in gestational age, estimated fetal weight, birth weight, or NICU admission rates. Stillbirth, prematurity, intrauterine growth restriction (IUGR), macrosomia, and neonatal mortality did not occur in either group. Conclusion: As evident from the current study, there were no differences between first and second-trimester COVID-19-infected and non-infected pregnant women according to maternal and neonatal outcomes regarding fetal growth complications, APGAR score, preterm Labour, NICU admission, Placental abnormalities, and Liquor abnormalities. Consequently, clinical characteristics of first and second-trimester COVID-19 in pregnant patients and neonates seem to be similar to those in non-pregnant infected adults.